State of the Facility Management Business In Bulgaria - Stefanov, Dragomir (Research Papers, 2019)
As part of the property management business the facility management is entering quickly our society. The main objective of the present study is through the methods of analyze and synthesize to summarize the results of an empirical questionnaire survey regarding the present state of FM business in Bulgaria. On this basis, conclusions have been made about the main trends in the development of the sector and some recommendations have been formulated for the active companies on this market.